Case Report: Severe Acute Pulmonary COVID-19 in a Teenager Post Autologous Hematopoietic Stem Cell Transplant - van der Velden, Fabian J. S.; van Delft, Frederik; Owens, Stephen; Llevadias, Judit; McKean, Michael; Pulford, Lindsey; Taha, Yusri; Williamson, Grace; Campbell-Hewson, Quentin; Hambleton, Sophie; Payne, Rebecca; Duncan, Christopher; et al. (Frontiers in Pediatrics, 2022)
Pulmonary COVID-19 infection in children is generally described as mild, and COVID-19 infection in immunocompromised children are observed as generally mild as well. A small proportion of pediatric patients will become critically ill due to (cardio)respiratory failure, and require intensive care treatment. We report the case of a teenager with Hodgkin’s lymphoma who acquired SARS-CoV-2 (detected by PCR) on the day of her autologous stem cell transplant and developed acquired respiratory distress syndrome, successfully treated with a combination of antivirals, immunomodulation with steroids and biologicals, and ECMO.